Interactions of the EGFR juxtamembrane domain with PIP2-containing lipid bilayers: insights from multiscale molecular dynamics simulations - Abd Halim, Khairul Bariyyah; Koldsoe, Heidi; Sansom, Mark S.P. (Elsevier, 2015)
The epidermal growth factor receptor (EGFR) is the best characterised member of the receptor tyrosine kinases, which play an important role in signalling across mammalian cell membranes. The EGFR juxtamembrane (JM) domain is involved in the mechanism of activation of the receptor, interacting with the anionic lipid phosphatidylinositol 4,5-bisphosphate (PIP2) in the intracellular leaflet of the cell membrane.Multiscale MD simulations were used to characterize PIP2-JM interactions. Simulations of the transmembrane helix plus JM region (TM-JM) dimer (PDB:2M20) in both PIP2-containing and PIP2-depleted lipid bilayer membranes revealed the interactions of the JM with PIP2 and other lipids.